How Will Extension Contribute to the Sustainable Development Goals? A Global Strategy and Operational Plan - Kristen Davis (Journal of International Agricultural and Extension Education, 2016)
Extension remains a critical institution for supporting rural livelihoodsand the Sustainable Development Goals. The Global Forum for Rural Advisory Services (GFRAS) recently launched a ten-year strategic framework and five-year operational plan, both aligned to the Sustainable Development Goals. The strategy was developed using a series of online and face-to-face consultations within the Forum, with expert feedbackat various stages. Using both an agricultural innovation systems and a capacity development framework, the strategy outlines strategic fields of action at three levels –individual, organizational, and system. The strategic fields of action include advocacy and support for increased investment in extension; professionalization; and knowledge generation and exchange. Activities in each strategic field will strengthen capacities at the three levels. For each strategic field, there are expected high-level strategic outcomes (changes in behavior) to which GFRAS will contribute.The strategy is accompanied by a five-year operational plan, which guides the GFRAS community on how to implement the strategic framework. Though thesedocuments, GFRAS can effectivelysupport the international extension community to contribute to the Sustainable Development Goals
Keywords: extension; advisory services; sustainable development goals; strategy